2014
DOI: 10.1051/0004-6361/201323130
|View full text |Cite
|
Sign up to set email alerts
|

Very deep images of the innermost regions of theβPictoris debris disc atL

Abstract: Context. Very few debris discs have been imaged in scattered light at wavelengths beyond 3 μm because the thermal emission from both the sky and the telescope is generally too strong with respect to the faint emission of a debris disc. We present here the first analysis of a high angular resolution image of the disc of β Pictoris at 3.8 μm. Aims. Our primary objective is to probe the innermost parts of the β Pictoris debris disc and describe its morphology. We performed extensive forward modelling to correct f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 39 publications
(70 reference statements)
6
49
0
Order By: Relevance
“…As a result, these regions should experience both more frequent and more violent (i.e., destructive) impacts. This 6 AU distance also roughly corresponds to the best resolution obtained on resolved images of debris discs (see, for example, Milli et al 2014, for the archetypal β Pictoris system). Last but not least, 6 AU is also the location where a high level of dustiness has been observed around HD 172555, one of the best known systems with high-luminosity excesses (Lisse et al 2009;Johnson et al 2012).…”
Section: Setupsupporting
confidence: 69%
“…As a result, these regions should experience both more frequent and more violent (i.e., destructive) impacts. This 6 AU distance also roughly corresponds to the best resolution obtained on resolved images of debris discs (see, for example, Milli et al 2014, for the archetypal β Pictoris system). Last but not least, 6 AU is also the location where a high level of dustiness has been observed around HD 172555, one of the best known systems with high-luminosity excesses (Lisse et al 2009;Johnson et al 2012).…”
Section: Setupsupporting
confidence: 69%
“…Previous studies of the scale height of debris disks have demonstrated a degeneracy between vertical structure, radial structure, and viewing geometry (e.g. Milli et al 2014). For example, it can be difficult to distinguish a disk that is vertically thin but slightly inclined from one that is vertically broad but perfectly edge-on.…”
Section: Discussionmentioning
confidence: 99%
“…In that case, the Henyey-Greenstein g coefficient is an additional free parameter that can be used to quantify the anisotropy of scattering. Because the star subtraction is performed using ADI, the disc can be significantly self-subtracted (Milli et al 2012), and we implement the forward-modelling technique already described in Milli et al (2014) for β Pictoris to retrieve the best disc parameters. The results are shown in Table 2.…”
Section: Constraints From Unpolarised Observations At Lmentioning
confidence: 99%